Structural modification and biological activity studies of tagitinin C and its derivatives. (16th July 2021) - Au, Thi Hang; Skarbek, Charles; Pethe, Stephanie; Labruere, Raphael; Baltaze, Jean-Pierre; Nguyen, Thi Phuong Hoa; Vu, Thi Thu Ha; Vo-Thanh, Giang
Abstract: The Michael addition reaction of amines, phosphonates and thiols to Tagitinin C containing in its structure an α-methylene-γ-lactone motif and two α, β-unsaturated ketone systems has been described. 27 Tagitinin C derivatives were synthesized and isolated in good to excellent yield (up to 99% yield) under mild reaction conditions. The biological activity of Tagitinin C and its derivatives were evaluated against three human cancer cell lines (breast human cancer cells MCF-7, breast human cancer cells multi-resistant to drugs MCF7-MDR, pancreas cancer cells MiaPaCa-2) and on normal cell line (HEK-293) as control. We showed that the biological activity of Tagitinin C derivatives is remained. These compounds presented an enhanced water solubility that could improve their bioavailability and their pharmacological profiles. Graphical abstract: Image 1